HUBUNGAN MOTIVASI DENGAN PELAKSANAANPERAWATAN PASIEN PASCA STROKERSUP DR. M.DJAMILPADANG 2016 - Melti Suriya (Menara Ilmu, 2017)
Stroke survivors continues to increase each years , the prevalence of stroke in the United States85 % of the 500 million people. Indonesia increased stroke by 57.9 % per year . Hospital Dr.M. Djamil Padang stroke in 2015 is 120 people. This study aims to determine the relationshipof motivation with the implementation of post- stroke patient care at Hospital Dr. M. DjamilPadang 2016. This type of research is descriptive analytic study in Hospital Dr. M. DjamilPadang with Cross Sectional approach. When the study in August 2016 in Hospital Dr. M.Djamil Padang. The sampling technique is accidental sampling with a sample of 55 people.Data were processed using univariate and bivariate analysis. The results showed 52.7% ofrespondents with low motivation, 54.5% implementation of the post-stroke patient care at theDr. M. Djamil Padang unfavorable. There is a significant relationship of motivation and careof post-stroke value of p = 0.002 (p <0.05).There is a relationship between motivation andimplementation of post-stroke care. Suggested can provide information and feedback tohospitals in implementing health care professional and to improve the degree of health servicein post-stroke patients, and to provide resources for familiesKeywords: motivation, care post-stroke